Enhanced interphase between epoxy matrix and carbon fiber with carbon nanotube-modified silane coating - Yu, Bin (2016)
Multiwalled carbon nanotubes are incorporated into the silane coating on fiber surface to enhance the interfacial bonding of carbon fiber reinforced epoxy composite. The results of microbond tests show that the interfacial shear strength of the prepared hybrid composites can be significantly increased by up to 26.3% compared with that of common composite. In contrast, the addition of carbon nanotubes into epoxy matrix demonstrates a distinctly weaker effect on enhancing the interphase between neat silane coated carbon fiber and matrix. This discrepancy can be attributed to the densification of CNT forest within the interphase during the forming of nanocomposite coating. Based on our experimental study, the carbon nanotube-based modification of silane coating on fiber surface is considered as a more efficient approach than the widely reported carbon nanotube-based tuning of matrix for hybrid composites, at the aspects of reinforcing effect, cost saving and process complexity.